2017
DOI: 10.1111/cote.12276
|View full text |Cite
|
Sign up to set email alerts
|

An innovative approach to the preparation of coloured and multifunctional silk material with the natural extracts from chestnut shell and black rice bran

Abstract: In order to reutilise the byproducts of foods and crops to benefit the environment and economise on resources, the natural extracts from chestnut shell and black rice bran were applied in the simultaneous dyeing and multifunctionalisation of silk fabrics. In this work, the influence of pH value on dyeing properties was studied. The effects of the ratio of chestnut shell and black rice bran extracts and the application of mordants (aluminium potassium sulphate and ferrous sulphate) on the dyeing performance as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…It was reported that all anthocyanin contain flavylium cation (Castaneda‐Ovando, de Lourdes Pacheco‐Hernández, Páez‐Hernández, Rodríguez, & Galán‐Vidal, ). However, the anthocyanin from rice bran was also found to contain flavylium cation within the wide pH range (Jia, Jiang, Liu, & Wang, ). A similar type of result was observed by the other researchers (Foo & Hameed, ; Zhou, Zhang, & Zhou, ).…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that all anthocyanin contain flavylium cation (Castaneda‐Ovando, de Lourdes Pacheco‐Hernández, Páez‐Hernández, Rodríguez, & Galán‐Vidal, ). However, the anthocyanin from rice bran was also found to contain flavylium cation within the wide pH range (Jia, Jiang, Liu, & Wang, ). A similar type of result was observed by the other researchers (Foo & Hameed, ; Zhou, Zhang, & Zhou, ).…”
Section: Resultsmentioning
confidence: 99%
“…The vibrations of active components (C3G and P3G), which were the main components of rice bran, were different between before and after by PEF-AWE. Both of before and after PEF-AW displayed peak vibrations of the hydroxy groups at 3292 cm −1 (O–H stretching), which were the characteristic of phenolic ring 36 , 37 . Smaller peak intensities were noticed on the spectral data of the rice bran of BRG after extraction due to the lower concentration of hydroxy groups of phenols which rich in C3G and P3G.…”
Section: Discussionmentioning
confidence: 99%
“…According to Otutu et al [20], dye extraction of colourants at 70°C for 4 h is applicable to produce an optimum amount of natural dye in water [21]. Figures 1 -10 show the effects of extraction temperature and time on the extracts.…”
Section: Dye Extractionmentioning
confidence: 99%